Липофильность и фармакологическая активность производных мочевины - Новожеева Т. П.; Столярова К. В.; Ахмеджанов Р. Р. Рафик Равильевич; Бакибаев А. А. Абдигали Абдиманапович; Хоружая Т. Г.; Саратиков А. С. (1997, 1997)
В фонде НТБ ТПУ отсутствует